Analysis of the three-phase state in biological hydrogen production from coal. (21st August 2020) - Xia, Daping; Yan, Xiatong; Su, Xianbo; Zhao, Weizhong
Abstract: The production of biohydrogen from coal is a new research direction in the bioengineering of coalbed methane. In order to study the transformation process and mechanism of the gas-liquid-solid tripe phase in biohydrogen production from coal, a biohydrogen production experiment from low-rank coal is carried out under laboratory conditions. The results show that: The daily gas production of hydrogen reaches a peak value of 1.23 mL/g on the fifth day. The cumulative hydrogen production is 6.24 mL/g. The pH of the liquid products gradually decreases to 5, and the Eh gradually increased from −180 to −50 mV during the experiment. The peak value of lignin degradation rate is 0.42% on the 7th day. The chemical oxygen demand (COD) first increases and then decreases. The highest COD is 4068 mg/L, and the final COD degradation rate is 46.3%. The peak values of cellulase are 0.021 mg/(mL h) and 0.223 mmol H2 /(min mg) at 3 d later than that of hydrogenase. The absorbance of bacterial turbidity first increases and then decreases, with the community structure proving that the hydrolytic bacteria are dominated by Acinetobacter, Comamonas, Intestinimonas, and some fermentation bacteria, including Macellibacteroides . The changes of carbon, oxygen, nitrogen, sulfur and functional groups of carbon and oxygen in coal are obvious, with aliphatic carbon (methoxy, carbonyl, and so on) representing the main part of the biochemical reaction in the macromolecular structure of coal. The analysis of the three-phase state in the process of coal hydrogen production is helpful to study the mechanism of hydrogen production by coal fermentation from different perspectives, and also provides a reference for the promotion of coal hydrogen production by fermentation in the next step. Graphical abstract: Image 1 Highlights: Biohydrogen production from coal is higher than in general hydrogen making technique. Change law of liquid phase parameters keep consistent with the hydrogen generation. Acinetobacter, Comamonas, and Intestinimonas are the dominant genus. Aliphatic carbon in coal makes a positive contribution to biohydrogen production. Biohydrogen production process usually accompanies the conversion of three phases.